2019
DOI: 10.3390/cells8030212
|View full text |Cite
|
Sign up to set email alerts
|

Mycoplasma genitalium Infection and Chronic Inflammation in Human Prostate Cancer: Detection Using Prostatectomy and Needle Biopsy Specimens

Abstract: The evidence of association between sexually transmitted infection and prostatic inflammation in human prostate cancer (PCa) is limited. Here, we sought to examine the potential association of prostatic infection with the inflammatory environment and prostate carcinogenesis. We screened surgical and biopsy specimens from 45 patients with PCa against a panel of sexually transmitted infection-related organisms using polymerase chain reaction and examined the severity of intraprostatic inflammation by pathologic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
42
1
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(49 citation statements)
references
References 26 publications
3
42
1
3
Order By: Relevance
“…Miyake et al [59] found that the rate of extensive prostate disease was higher in those with Mycoplasma genitalium infection compared to those who did not have M. genitalium infection. M. genitalium is a clinically important sexually transmitted pathogen, which causes diseases that https://doi.org/10.4111/icu.2020.61.S1.S43…”
Section: Specific Microbial Bacteria and Prostate Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…Miyake et al [59] found that the rate of extensive prostate disease was higher in those with Mycoplasma genitalium infection compared to those who did not have M. genitalium infection. M. genitalium is a clinically important sexually transmitted pathogen, which causes diseases that https://doi.org/10.4111/icu.2020.61.S1.S43…”
Section: Specific Microbial Bacteria and Prostate Cancermentioning
confidence: 99%
“…The studies exploring the specific microorganism and prostate cancer risk discussed above are summarized in Table 1 [44,53,54,59,60].…”
Section: Specific Microbial Bacteria and Prostate Cancermentioning
confidence: 99%
“…A similar study by Miyake et al, 2019 screened 45 prostate cancer and 33 BPH patient tissue specimens for various sexually transmitted infectious agents using PCR. Out of the seven organisms that were tested for, namely; Neisseria gonorrhoeae, Chlamydia trachomatis, Mycoplasma genitalium, Mycoplasma hyorhinis, Ureaplasma urealyticum, HPV16, and HPV18, only Mycoplasma genitalium was independently associated with prostate cancer and with high Gleason scores [39]. The findings from these studies indicate that prostate cancerous tissue harbor different microbial species, which could be linked to prostatic inflammation and carcinogenesis.…”
Section: Microbiome In Prostate Tissue Microenvironmentmentioning
confidence: 91%
“… Banerjee S et al,2019 [ 38 ] Microarray metagenomics analysis of formalin-fixed tissue from 50 prostate cancer patients and 15 patients with BPH The most predominant bacteria belonged to the following phyla; Proteobacteria, Firmicutes, Actinobacteria, and Bacteroidetes respectively. Among the viruses isolated, 41% were known tumorigenic viruses, including high-risk human papillomavirus (HPV 16&18), and human cytomegalovirus (HCMV) Miyake M et al, 2019 [ 39 ] 45 prostate cancer and 33 BPH tissue specimens were screened for sexually transmitted infectious agents using PCR Mycoplasma genitalium was the only organism independently associated with prostate cancer and with high Gleason scores Shrestha E et al 2018 [ 44 ] Assessed the urinary microbiome of 135 men undergoing prostate needle biopsy Corynebacterium, Staphylococcus , and Streptococcus species were the most predominant in both positive and negative biopsy cases. No species was significantly associated with prostate cancer.…”
Section: Introductionmentioning
confidence: 99%
“…To reduce the impact of close proximity of the compared regions and the field effect thoroughly, Miyake et al examined 45 prostate cancer patients who underwent robotic prostatectomy and 40 benign prostatic hyperplasia patients. The rate of Mycoplasma genitalium infection in the prostate cancer patients was higher than in the benign prostatic hyperplasia patients (Miyake et al, 2019). The above microbial differences between the tumoral lesions and the nonneoplastic tissues indicated that microbes might be novel biomarkers and/or therapeutic targets for prostate cancer.…”
Section: Relations Between Microbes In the In Situ Tissue And Tumors mentioning
confidence: 98%